Analisis Determinan Pemberian Pendidikan Kesehatan Dengan Metode PAKEM (Partisipatif, Aktif, Kreatif, Efektif, Menyenangkan) Terhadap Upaya Pencegahan Kenakalan Remaja: An Analysis of the Determinants of Health Education Provision Using the PAKEM Method (Participatory, Active, Creative, Effective, and Enjoyable) on Juvenile Delinquency Prevention Efforts - Helmika Apri; Yullyzar; Syarifah Masthura; Muhammad Armiyadi; Riyan Mulfianda (MPI Press, 2026)
Introduction: Juvenile delinquency is a prevalent behavioral issue among adolescents aged 12–15 years. During this developmental stage, strong peer loyalty and identity exploration may increase the risk of engaging in deviant behaviors such as truancy, bullying, fighting, smoking, substance abuse, and other misconduct. Schools play a strategic role in preventing such behaviors through effective health education approaches. The PAKEM method (Participatory, Active, Creative, Effective, and Joyful Learning) is a student-centered learning strategy designed to enhance engagement and behavioral awareness.Objective: This study aimed to analyze the relationship between health education using the PAKEM method and efforts to prevent juvenile delinquency at SMP Negeri 5 Takengon.Methods: This study employed a quantitative analytic correlational design with a cross-sectional approach. The population consisted of 245 students, with 164 respondents selected using purposive sampling based on inclusion and exclusion criteria. Data were collected using structured questionnaires and analyzed using the Chi-Square test with a significance level of p < 0.05. Results: The statistical analysis showed a significant relationship between the implementation of the PAKEM method and juvenile delinquency prevention efforts (p = 0.000; p < 0.05). Students who received high-level PAKEM-based education demonstrated better prevention efforts compared to those in the lower category.Conclusion: The PAKEM method is significantly associated with improved efforts to prevent juvenile delinquency. This learning approach can be recommended as an effective preventive strategy in school based health education programs.